Persian-Punjabi/Urdu Identities of Traditional Geometrical Patterns Lost During the Colonial Rule of the Punjab (1849–1947) - Shahbaz Khan, Nadhra (Manazir Journal, 2022)
Annexation of the Punjab by the British in 1849 brought about major modifications to the local visual culture. Expecting Indian crafts to remain frozen in time (for several reasons), the colonial administrators and art critics disapproved the changes employed by the craftsmen in their wares to cater to the new ruling class. Among the corrective measures adopted by the government to revive the ‘dying’ Indian art and craft, art schools were set up and surveys were conducted to publish illustrated monographs on individual crafts bringing once strictly guarded trade secrets out in the public. By the late nineteenth century, the ‘native craftsmen’ or mistrīs themselves emerged as authors of illustrated craft manuals carrying instructions in all three important vernaculars, Gurmukhi, Urdu and Sanskrit mixed with some English terms and designs. The most interesting among these publications are a few woodcarver’s manuals that laboriously enumerate a wide range of geometric designs for both architecture and furniture. Each shape, its construction methods and titles are given in an interesting mix of the three vernaculars. These terms were also mentioned by John Lockwood Kipling, the first Principal of the Mayo School of Industrial Art (1876-1893) in his essay on wood carving but abandoned by the time Percy Brown (1897-1909) took over. Except for some, today most of these terms and construction methods are unknown even to the traditional craftsmen of the Punjab. This paper aims to trace the history of traditional geometrical patterns going as far back as Mughal times (sixteenth to eighteenth centuries), their references in manuals published by local craftsmen during the colonial rule and the role of British art educators on social memory.